The Influence of Islamic Brand Engagement as A Moderation Variable on Brand Loyalty in Bank Syariah Indonesia Customers - Warsito, Chandra; Suryandari, Sofia Yustiani; Pujiati, Pujiati; Farhah, Nida Umi; Ab. Wahab, Norailis (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to determine the ability of Islamic brand attachment to moderate the influence of brand personality, customer satisfaction, and aura brand customer religiosity towards brand loyalty in Indonesian Islamic banks. Primary data collection was conducted by purposive sampling with a sample size of 320 questionnaire responses collected. from Bank customers Indonesian Sharia is domiciled in Yogyakarta, Surakarta, Purwokerto, Semarang, Jakarta, Bandung, Banten and Surabaya. The relationship between personality variables brand, satisfaction customers, And aura brand religious Customer to brand loyalty was analyzed using Structural Equation Modeling (SEM) from the Wap PLS program package. Results study empirical show there is influence personality brand, satisfaction customers, and the aura of a religious brand customers towards brand loyalty of Bank Syariah Indonesia. The test results show that Brand personality, Customer satisfaction , and . Brand religious aura is influential positive to brand loyalty on Customer Bank Sharia Indonesia. Islamicbrand engagement is able to moderate the relationship between brand personality and brand loyalty in Bank Syariah Indonesia customers. But Islamic brand engagement is not able to moderate the relationship between customer satisfaction and brand religious aura towards brand loyalty . Customer Bank Sharia Indonesia. Recommendation managerial Which produced from This research is that Bank Syariah Indonesia must focus on continuously improving brand personality, customer satisfaction, and religious brand aura because they are directly correlated with customers